PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KEJA KARYAWAN (STUDI PADA PT SURYA DUMAI AGRINDO KABUPATEN BENGKALIS) - Putri Bestari Situmorang; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research conducted at PT Surya Dumai Agrindo Bengkalis. As for the purpose of this study was to determine the effect of organizational culture and organizational commitment to employee job satisfaction (study at PT Surya Dumai Agrindo Bengkalis). Organizational culture and organizatinal commitment as the independent of variable (X1X2) while employee job satisfaction as the dependent variable.The problem in this research is the fluctuation of employee turnover and entry accompanied by employee absences that increase every year. Seen from the Labor Turn Over and company absentee data. The sample of this study was taken as many as 86 respondents using purposive sampling techniques from the population calculated using the Slovin formula. Data analysis in this study used multiple linear regression analysis which was processed using the SPSS program. Data collection is done by distributing questionnaires.The results of test carried out show that organizational culture and organizational commitment have a positive and significant effect on job satisfaction (study at PT Surya Dumai Agrindo Bengkalis). Keywords : Organizational Culture, Organizational commitment